Evaluation of hydrodynamic chromatography coupled with UV-visible, fluorescence and inductively coupled plasma mass spectrometry detectors for sizing and quantifying colloids in environmental media. - Allan Philippe; Gabriele E Schaumann (PLoS ONE)
In this study, we evaluated hydrodynamic chromatography (HDC) coupled with inductively coupled plasma mass spectrometry (ICP-MS) for the analysis of nanoparticles in environmental samples. Using two commercially available columns (Polymer Labs-PDSA type 1 and 2), a set of well characterised calibrants and a new external time marking method, we showed that flow rate and eluent composition have few influence on the size resolution and, therefore, can be adapted to the sample particularity. Monitoring the agglomeration of polystyrene nanoparticles over time succeeded without observable disagglomeration suggesting that even weak agglomerates can be measured using HDC. Simultaneous determination of gold colloid concentration and size using ICP-MS detection was validated for elemental concentrations in the ppb range. HDC-ICP-MS was successfully applied to samples containing a high organic and ionic background. Indeed, online combination of UV-visible, fluorescence and ICP-MS detectors allowed distinguishing between organic molecules and inorganic colloids during the analysis of Ag nanoparticles in synthetic surface waters and TiO₂ and ZnO nanoparticles in commercial sunscreens. Taken together, our results demonstrate that HDC-ICP-MS is a flexible, sensitive and reliable method to measure the size and the concentration of inorganic colloids in complex media and suggest that there may be a promising future for the application of HDC in environmental science. Nonetheless the rigorous measurements of agglomerates and of matrices containing natural colloids still need to be studied in detail.